Aromatic glycosides from Eulophia andamanensis. (April 2021) - Maliwong, Jedsada; Chimnoi, Nitirat; Thamniyom, Wassapol; Ruchirawat, Somsak; Kanchanapoom, Tripetch
Graphical abstract: Two new aromatic glycosides were isolated from Eulophia andamanensis . Highlights: Two new aromatic glycosides were isolated from Eulophia andamanensis . The secondary metabolites of Eulophia andamanensis were reported for the first time. Glucosyloxybenzyl deivatives were related to isolated compounds from the same subfamily. Abstract: Two new phenolic glycosides, eulophiosides A and B (3, 4 ), were isolated from Eulophia andamanensis in addition to six known compounds. The known compounds were identified as gastrodin (1 ), vitexnegheteroin A (2 ), grammatophylloside A (5 ), grammatophylloside B (6 ), pleionoside E (7 ), and pleionoside F (8 ). Their structures were determined based on the physical data and the spectroscopic evidence including 1D and 2D NMR experiments.